Notes on the diet of birds in the Free State and Lesotho, Southern Africa - Kopij, Grzegorz (Biodiversity Observations, 2014)
Observations on the diet of 45 species from the Free State province, South Africa, and Lesotho, are presented. To date, little data was available on the diet of birds in these areas, especially in Lesotho. For most records, the following data are provided: species name; place and data of observations; number of foraging birds; name of food objects.